Where there is no vet - Forse, Bill (CTA / Macmillan / Oxfam, 1999)
The aim of this book is to help farmers keep their animals healthy, recognising the problems they can deal with themselves and those needing veterinary attention. It is also intended for teachers, NGO workers, extension officers and veterinary assistants. The animals covered include: cattle, buffaloes, goats, sheep, pigs, horses, donkeys, camels, rabbits and poultry.